2014
DOI: 10.1097/mbc.0000000000000231
|View full text |Cite
|
Sign up to set email alerts
|

Patients with cirrhosis show a relative increase in thrombin generation that is correlated with lower antithrombin levels

Abstract: Predicting the risk of bleeding or thrombosis in cirrhotic patients is difficult due to reduced levels and dysregulation of both procoagulant and anticoagulant factors. We utilized thrombin generation and microvesicle analysis to better understand the regulation of haemostasis in cirrhotic patients. We studied 24 patients with cirrhosis vs. 21 healthy controls. Cirrhotic patients had reduced prothrombin activity (40 ± 9 vs. 112 ± 15), protein C activity (36 ± 10 vs. 114 ± 19) and antithrombin activity (43 ± 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
9
0
3
Order By: Relevance
“…Although many studies have investigated the role of cirrhotic plasma in PCA , relatively little is known about the contribution of activated blood cells, especially erythrocytes and leucocytes. Our results showed that PS exposure on BCs progressively increased with Child–Pugh category.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many studies have investigated the role of cirrhotic plasma in PCA , relatively little is known about the contribution of activated blood cells, especially erythrocytes and leucocytes. Our results showed that PS exposure on BCs progressively increased with Child–Pugh category.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that cirrhotic patients have a higher risk of venous thromboembolism than healthy subjects . Other studies have shown that resistance to thrombomodulin, increased factor VIII to protein C ratio, and lower level of antithrombin in cirrhosis may lead to increased thrombosis risk . However, excess exogenous phospholipid was added during the course of these studies.…”
mentioning
confidence: 99%
“…23 Concentrations of AT decline in cirrhosis with measured activities of 43 6 14% relative to 109 6 10% in healthy controls. 24 This concomitant decline in anticoagulant proteins, specifically AT, accompanied by elevated levels of FVIII may explain the ability of cirrhotic patients to generate thrombin concentrations equivalent to healthy persons. 25,26 Dysfibrinogenemia is common in cirrhosis, occurring in up to 70% of patients secondary to the addition of excess sialic acid residues to fibrinogen, impairing its ability to assemble properly.…”
Section: Pltsmentioning
confidence: 99%
“…The prothrombin time (PT) 3 and partial thromboplastin time (PTT) are useful assays for evaluation of coagulation factor levels and for monitoring anticoagulant therapy with warfarin and heparin, but they are of less value for predicting risk of thrombosis or bleeding in patients with acquired hemostatic defects. As new anticoagulant drugs become available and pathophysiologic mechanisms of abnormal hemostasis are unveiled, it is clear that new laboratory tests are needed to support drug monitoring, establish diagnosis, and develop therapeutic strategies.…”
mentioning
confidence: 99%
“…Altered TGA results have been described in several clinical situations, including cirrhosis, trauma, cardiopulmonary bypass surgery, stroke, sepsis, and the use of oral anticoagulants (3)(4)(5)(6)(7)(8). There is some evidence suggesting that TGA is a better indicator of overall hemostatic capability and could provide information for transfusion support in patients with cirrhosis and coagulation factor replacement in patients with hemophilia with and without inhibitors (9)(10)(11).…”
mentioning
confidence: 99%